(untitled) (Research, Society and Development, 2020)
The nutrition of cancer patients in palliative care is essential, since cancer leads to deterioration of nutritional status, leading to a nutritional imbalance that can progress to severe malnutrition depending on the extent of the tumor, affecting the patient’s prognosis. It is a descriptive study, of the type integrative literature review, of a qualitative character, the search occurred in the databases: LILACS, SCIELO and BDENF, via VHL, and Scholar Google. The articles were collected in the period of September 2020. The descriptors were used: Nutritional therapy, Oncology and Palliative care. After applying the eligibility criteria, 8 studies remained. Nutritional therapy helps to reduce symptoms related to treatment, as well as weight loss, prolonging survival and improving the patient’s quality of life. It should be performed as early as possible. It was concluded that it is essential that the professional has knowledge of the best therapy in order to provide well-being and avoid unnecessary interventions that may cause more suffering to the patient.